Anesthesia management for ENT surgery in a child with X‐linked pyruvate kinase deficiency. Issue 4 (18th January 2021) - Hau, Vickie; Bonilla‐Velez, Juliana; Low, Daniel
Abstract: Pyruvate dehydrogenase complex deficiency (PDCD) is a rare X‐linked disorder that affects glucose metabolism. There are several case reports describing the anesthetic management of patients with PDCD. This is the first case report to describe the anesthetic management of a PDCD patient requiring spontaneous ventilation using dexmedetomidine and ketamine.